Decay-accelerating factor (CD55), a glycosylphosphatidylinositol-anchored complement regulatory protein, is a receptor for several echoviruses. - Bergelson, J M (1994)
Echoviruses are human pathogens belonging to the picornavirus family. Decay-accelerating factor (DAF) is a glycosylphosphatidylinositol (GPI)-anchored surface protein that protects cells from lysis by autologous complement. Anti-DAF monoclonal antibodies prevented echovirus 7 attachment to susceptible cells and protected cells from infection. HeLa cells specifically lost the capacity to bind echovirus 7 when treated with phosphatidylinositol-specific phospholipase C, an enzyme that releases GPI-anchored proteins from the cell surface, indicating that the virus receptor, like DAF, is a GPI-anchored protein. Although Chinese hamster ovary cells do not bind echovirus 7, transfectants expressing human DAF bound virus efficiently, and binding was prevented by pretreatment with an anti-DAF monoclonal antibody. Anti-DAF antibodies prevented infection by at least six echovirus serotypes. These results indicate that DAF is the receptor mediating attachment and infection by several echoviruses.